The Therapeutic Implications of Biomarkers Testing in Non-small Cell Lung Cancer in Middle- and Low-income Country: The Example of Morocco - Aazzane, Oussama; Fathi, Sofia; Meryem, Charkaoui; Abdelkader, Acharki; Souha, Sahraoui; Nadia, Benchakroun; Hassan, Fellah; Mehdi, Karkouri (Asian Pacific Journal of Environment and Cancer, 2024)
Introduction: The Identification of PD-L1, EGFR and ALK status is essential to guide personalized treatment of NSCLC. The objective of our study is to evaluate the implication of changing the therapeutic protocol on the prognosis of Moroccan patients with NSCLC. Methods: Between January 2019 and February 2023, 96 patients with NSCLC were recruited. Results: In our population, the patients were treated with different first-line protocols: 83.34% (N=80) with neo-adjuvant chemotherapy, 14.58% (N=14) with immunotherapy and 2.08% (N=2) with targeted therapy. Of the 82 patients who received neo-adjuvant chemotherapy (N=80), 24 were able to switch to immunotherapy. While, the 2 patients who received targeted therapy beforehand also switched to immunotherapy. The influence of the number of chemotherapy (Chemo) cycles on vital status and overall survival (OS) of the 24 patients who switched from their initial protocol to immunotherapy (IO) showed that patients who received IO after completing the 4 or 5 cycles of chemo had a good OS, with a mean of 29.07 months. In comparison, patients who received less than 4 cycles of chemo had a mean OS of 14.70 months, while those who received more than 5 cycles of chemo had a mean OS of 21.38 months. Furthermore, the association between change in treatment protocol and patient vital status was significant (p=0.013). However, there was a significant difference in OS between patients who maintained the treatment protocol (mean OS=12.43 months) and those who changed the protocol (mean OS=24.01 months) (p=0.000). Multivariate analysis indicated that maintaining the initial therapeutic protocol was independently associated with a reduced OS (p=0.003). Conclusion: Our results highlight the impact of changing the protocol on the OS of NSCLC patients taking into account the importance of choosing the right timing to switch to IO based on the number of prior chemo cures.